Penerapan Pendekatan Taktis Dalam Meningkatkan Keterampilan Bermain Sepakbola di SSB Lakemba Muda FC - Muhammad Gilang Ramadhan; Oman Hadiana (Universitas Muhammadiyah Kuningan, 2024)
Study This motivated Because Still Lots SSB Lakemba Young FC players in aspect skills play especially when taking decision in the field like example of a ball that should be passed but player carry the ball without clear goals .​ Quality technique base player not enough so well , as example Lots player when not passing the ball appropriate toward colleague team. There are also player when No less control of the ball give support by searching strategic position , so​ makes it easier other players to pass the ball. Research purposes This is For know effectiveness application of the approach model tactical in increase skills play game football . Method used is experiment with a one group pretest and posttest design . Deep sample study This is SSB Lakemba Muda FC players totaling 20 people. Retrieval technique sample using random sampling. Technique for analyze the results data study using paired sample test. Research result show that application of the approach model tactical give very significant impact to skills play game football . Study furthermore Can carried out using the Approach model Tactical For solve problem technical skills​ play on the game football .